Community-wide prevalence and intensity of soil-transmitted helminthiasis and Schistosoma mansoni in two districts of Sierra Leone. - Cara Tupps; Ibrahim Kargbo-Labour; Jusufu Paye; Sanjaya Dhakal; Mary H Hodges; Alexander H Jones; Stacy Davlin; Mustapha Sonnie; Sallay Manah; Rubina Imtiaz; Yaobi Zhang (Public Library of Science (PLoS), 2022)
In Sierra Leone, nationally powered school-based surveys have documented significant progress in the control of soil-transmitted helminthiasis (STH) and schistosomiasis. In order to assess the district-level prevalence and intensity of infection among key at-risk groups outside of school age children (SAC), we conducted a multi-stage, cluster-sample household survey in Bo and Kenema districts in May 2018. From both districts, we examined 1,282 pre-school age children (PSAC), 730 school age children (SAC), and 517 adults over 14 years (including 387 women of reproductive age, or WRA) for STH and Schistosoma mansoni infection using Kato Katz technique. In Bo, STH prevalence was 8.0% (95% Upper Confidence Limit 10.2%) in PSAC, 6.4% (95% Upper Confidence Limit 9.0%) in SAC, 14.1% (95% Upper Confidence Limit 17.4%) in all adults and 11.9% (95% Upper Confidence Limit 17.4%) in WRA. In Kenema, STH prevalence was 18.1% (95% Upper Confidence Limit 20.5%) in PSAC, 17.3% (95% Upper Confidence Limit 20.7%) in SAC, and 16.9% (95% Upper Confidence Limit 20.5%) in all adults and 16.9% (95% Upper Confidence Limit 22.6%) in WRA. Hookworm species were the most prevalent of STH in both districts overall. The overall prevalence of S. mansoni was <10% in Bo and <20% in Kenema, and was similar across age groups. No moderate or heavy intensity STH infections or heavy intensity S. mansoni infections, as per World Health Organization (WHO) classification, were detected in either district. Sanitation variables, such as toilet access and quality, were independently associated with STH and S. mansoni infection. In Kenema, STH prevalence in SAC was within the WHO-defined range for annual treatment, whereas a previous nationally-powered survey estimated it to lie within the range of treatment once per two years. By utilizing community-based sampling, we were able to assess prevalence among WRA and make recommendations based on current guidance from WHO. To continue toward elimination of STH and S. mansoni as a public health problem, resources should be mobilized to increase access to and uptake of improved sanitation at community and household levels.